The smartness of Climate Smart Agriculture in 4 points - Visser, Piet (Technical Centre for Agricultural and Rural Cooperation, 2019)
Piet Visser, Team Leader (Agribusiness and Value Chain) at CTA, shares his idea on the smartness of Climate Smart agriculture in 4 points.